1999
DOI: 10.1116/1.590823
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of a new ordered structural dopant source in InAs/(001) GaP heterostructures

Abstract: We report the characteristics of molecular-beam epitaxy grown InAs on highly lattice mismatched (001) GaP substrates. Strain relaxation in this system occurs at low thickness by the generation of a periodic two-dimensional square grid network of 90° misfit dislocations at the heterointerface. The very high interface dislocation density (∼1013 intersections/cm2) exerts a unique influence on the electronic properties of the system. An extended defect structure at the intersection of 90° misfit dislocations is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…8 Hall effect measurements performed on thin InAs layers yielded a sheet electron concentration of 10 13 cm -2 , which was invariant with layer thickness. 8 Hall effect measurements performed on thin InAs layers yielded a sheet electron concentration of 10 13 cm -2 , which was invariant with layer thickness.…”
Section: Undoped Inas Layersmentioning
confidence: 92%
“…8 Hall effect measurements performed on thin InAs layers yielded a sheet electron concentration of 10 13 cm -2 , which was invariant with layer thickness. 8 Hall effect measurements performed on thin InAs layers yielded a sheet electron concentration of 10 13 cm -2 , which was invariant with layer thickness.…”
Section: Undoped Inas Layersmentioning
confidence: 92%
“…We have previously proposed that the high interfacial sheet carrier density could be caused by a structural donor source at the intersection of misfit dislocations at the InAs/ GaP interface and have demonstrated a one-to-one correspondence between the density of the intersection sites and the observed N s . 19 Although the carriers in the bulk could also be related to dislocations, a one-to-one correspondence does not exist in this case. A simple calculation, based on an estimated constant dislocation density of 10 10 cm Ϫ2 and assuming complete ionization of all atoms along each dislocation line, yields a carrier density of ϳ5ϫ10 17 cm Ϫ3 , an order of magnitude higher than the extracted background concentration of 6ϫ10 16 cm Ϫ3 .…”
Section: A Variation Of Carrier Concentration With Thickness and Temmentioning
confidence: 90%
“…We have previously reported that such InAs films have unique electronic properties associated with interface misfit dislocation intersections, known as ''driedl'' defects, 6 including interface Fermi-level pinning, interface electron generation and scattering, and no carrier freeze out at low temperatures. 1 Here, we report the correlation between the threading dislocation intersection density profile and the carrier profile for InAs films. We have modeled the carrier profiles for these InAs films as a first-order approximation of the observed threading dislocation intersection densities.…”
mentioning
confidence: 97%
“…Owing to its high electron mobility and high electron saturation drift velocity, InAs is a good candidate for both IR photonic and high speed tetrahertz device applications. 1,2 This has motivated our group to pioneer the molecular beam epitaxy ͑MBE͒ of high quality InAs on GaP substrates, even though there is an 11% lattice mismatch between GaP and InAs. We have previously reported that such InAs films have unique electronic properties associated with interface misfit dislocation intersections, known as ''driedl'' defects, 6 including interface Fermi-level pinning, interface electron generation and scattering, and no carrier freeze out at low temperatures.…”
mentioning
confidence: 99%